EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA MI DARUL FALAH, DESA SIDOMULYO, KECAMATAN WATES, KABUPATEN KEDIRI - Wuryandari, Maria Magdalena Riyaniarti Estri; Purnamasari, Vivien Dwi (Universitas Mataram, 2025)
Healthy living is something that should be implemented by everyone, considering that the benefits it brings are many, ranging from work concentration, children's health and intelligence to family harmony. MI Darul Falah is a school that is the main target in the community service education program for Clean and Healthy Living Behavior (PHBS) because it is located quite far from urban areas, precisely in Sidomulyo Village, Wates District, Kediri Regency. This research aims to increase students' understanding and awareness at MI Darul Falah, Sidomulyo Village, Wates District, Kediri Regency, regarding the importance of Clean and Healthy Living Behavior (PHBS). The counseling was attended by 213 students from grades 1, 2, 3, 4, 5 and 6. The counseling method consisted of material delivered through lectures using power point media, and playing media for children. Education on Hand Washing with Soap (CTPS) was provided to classes 1, 2 and 3 totaling 118 students and education on brushing teeth properly was provided to classes 4, 5 and 6 totaling 95 students. Pre test and post test measurements were carried out to determine students' knowledge of CTPS material. The research results showed that the pre test score was 70.84% ​​and the post test score was 91.01%, so there was a significant increase in knowledge of 20.17% and there was a change in students' behavior in practicing brushing their teeth correctly. After attending education, students become more aware of the importance of maintaining personal and environmental cleanliness, as well as practicing healthy living habits, such as washing hands properly and brushing teeth properly in everyday life.